Pengaruh Pendidikan dan Pelatihan Kerja Terhadap Kinerja Karyawan PT. Buhler Indonesia - Farichatus Solichah; Iswati Iswati; Emilia Pranata (Jurnal Riset dan Inovasi Manajemen, 2024)
This research aims to determine the effect of education and job training on the performance of PT employees. Buhler Indonesia Tangerang – Banten. The approach used in this research is quantitative. The population in this study were all employees of PT. Buhler Indonesia, numbering 50 people. Sampling if the subjects to be studied are less than 50 people, it is best to take all of them. in this research is a multiple linear regression analysis technique with SPSS 26 software, the theme of this researcher is the influence of education and job training on the performance of PT employees. Buhler Indonesia. The second level of probability, namely job training, has a significant effect on the performance of PT employees. Buhler Indonesia